Developing E-Module of English Speaking Material Based on Merdeka Curriculum Using ISpring Suite 11 Application: Penelitian - Vella Fidia; Eka Agustina; Muhammad Muklas (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research aimed to design and develop teaching materials in the form of E-Modules Speaking as an alternative learning tool to improve speaking skill of students at the 10th grade of SMAS Kurnia Jaya. The design development method used the Research and Development (R&D) method using the ADDIE model. In the early stages, a needs analysis was conducted to gather students feedback regarding current learning methods. The E-Module Speaking was then created based on the analysis and design stages. After the E-module Speaking was developed, a validity test was carried out by 2 media experts and 2 material experts, and a practicality test was carried out by 1 teacher to test the feasibility of using the e-module. The results of the research show that this e-module was included in the valid criteria and was suitable for use in the process of learning to speak English, with a media expert validity percentage of 89% (very valid) and a material expert validity of 93% (very valid). It also fulfilled the practicality criteria with teacher practicality test scores of 88% (very valid). The E-Module Speaking was tested two trials, a small group and big group. The small group trial, conducted with 8 students, achieved a percentage of 91,25% (very high). Wheareas, the big group trial, conducted with 29 students achieve a percentage of 90% (very high). Students positive responses to the e-module speaking show that this learning media can be used as a tool to improve students' speaking skills.